Intensified Th9 Response is Associated with the Immunopathogenesis of Active Ulcerative Colitis. (3rd October 2018) - Shohan, Mojtaba; Sabzevary-Ghahfarokhi, Milad; Bagheri, Nader; Shirzad, Hedayatollah; Rahimian, Ghorbanali; Soltani, Amin; Ghatreh-Samani, Mahdi; Deris, Fatemeh; Tahmasbi, Kamran; Shahverdi, Elahe; Fathollahi, Fereshteh
ABSTRACT: Background : Ulcerative colitis (UC) is a chronic inflammatory disorder of the large intestine histologically characterized by indistinct sustained inflammatory responses. Genetical susceptibility and environmental factors' effects play the roles in disease occurrence and it can be life threatening if remains untreated. It seems that intensification of inflammatory responses in this condition is not restricted to a specific cell line of T lymphocytes. Our aim was to determine the number of T helper 9 (Th9) cells in inflamed colonic biopsies of UC patients. We also correlated it with interleukin (IL)-9 protein level in addition to certain genes expressions associated with Th9 phenotype. Methods : Expression of CD4 and IL-9 were evaluated by immunohistochemical staining. Enzyme linked immunosorbent assay (ELISA) was performed to determine the colonic expression of IL-9 protein and finally mRNA expressions of interferon regulatory factor 4 (Irf4), Smad2, and Smad3 were measured by real-time polymerase chain reaction (RT-PCR) as critical transcription factors of Th9 differentiation. Results : Number of Th9 cells was significantly increased in inflamed samples as compared with normal tissues. Also quantitative measurement of IL-9 by ELISA and mRNA expressions of Irf4, Smad2, and Smad3 showed notable correlative enhancements in patient's samples. Conclusion : Function and number of Th9 cells are up-regulated in the inflamed mucosa of UC patients as with the protein secretion of IL-9 and mRNA expressions of Irf4, Smad2, and Smad3, so Th9 cells and IL-9 may become remarkable therapeutic targets for IBD treatment in the future.